Epidural Anesthesia With Low Concentration Ropivacaine and Sufentanil for Percutaneous Transforaminal Endoscopic Discectomy: A Randomized Controlled Trial - Zhang, Lingling; Chang, Tao; Xu, Yaru; Jing, Qi; Zhao, Xuan; Li, Cheng (Frontiers in Medicine, 2020)
Introduction: Percutaneous transforaminal endoscopic discectomy is a simple and effective treatment for lumbar intervertebral disc herniation, and local anesthesia is often applied in this kind of surgery in many developing countries including China. However, many patients still feel excruciating pain under this condition. Epidural anesthesia with low-concentration ropivacaine has no impact on the muscle strength, and patients might follow surgeon well during operation. We hypothesize that epidural anesthesia is feasible for percutaneous transforaminal endoscopic discectomy. Methods: Two hundred patients with disc herniation who underwent percutaneous transforaminal endoscopic discectomy were randomized to receive either epidural anesthesia or local infiltration anesthesia. Primary outcome measures included the pain score, the cooperation degree and patients’ satisfaction. Mean arterial pressure and heart rate were also recorded. Results: Compared with local anesthesia group, visual analog scale scores, mean arterial pressure, and heart rate were significantly lower in the epidural anesthesia group (P< 0.05), and patients’ satisfaction was higher. There were no significant differences in the total operation time or blood loss between two groups. Conclusions: Epidural anesthesia with low-concentration ropivacaine and sufentanil is safe and effective for the percutaneous transforaminal endoscopic discectomy.